2006
DOI: 10.1021/cm052841g
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Selectivity of Ti-Based Photocatalysts (TiO2 and Microporous ETS-10 and ETS-4) by Playing with Surface Morphology and Electronic Structure

Abstract: In the first part of this work we report an exhaustive characterization of the bulk and surface properties of ETS-4 and ETS-10 microporous titanosilicates by means of combined N 2 volumetric measurements, SEM, IR, Raman, and UV-Vis techniques. The structure of the surface titanols, derived from literature XRD studies, is shown using a molecular graphic approach. UV-Vis titration experiments using H 2 O 2 , and catechol molecules, allowed us to directly measure the total number of available titanols (both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 82 publications
(171 reference statements)
1
92
0
1
Order By: Relevance
“…The smaller crystalline particle size and increased surface area of the material calcined only for 1 h appear to have enhanced the photocatalytic activity. Furthermore, even though neither TiO 2 nor Chlorophenol (CP) absorb visible light it has been reported that the TiO 2 -CP ads system has charge transfer bands that can absorb such radiation [54][55][56][57]. Kim and Choi have shown that charge carriers can be generated from the excitation of these charge transfer states and that there remains the possibility for a variety of photochemistries to result from reaction of these charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller crystalline particle size and increased surface area of the material calcined only for 1 h appear to have enhanced the photocatalytic activity. Furthermore, even though neither TiO 2 nor Chlorophenol (CP) absorb visible light it has been reported that the TiO 2 -CP ads system has charge transfer bands that can absorb such radiation [54][55][56][57]. Kim and Choi have shown that charge carriers can be generated from the excitation of these charge transfer states and that there remains the possibility for a variety of photochemistries to result from reaction of these charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Single-crystal Raman spectroscopy measurements also support the hypothesis that the partial dissociation of titania wires in ETS-10 by HF treatment produces the surface active sites ( Figure S8 in the Supporting Information). [3] Experiments on a single crystal provide useful information for elucidating the inherent heterogeneity of reaction processes occurring at the solid-liquid interface. Figure 3 shows an example of the influence of crystal defects on the photocatalytic oxidation of APF molecules.…”
Section: B)mentioning
confidence: 99%
“…[1][2][3] In a defect-free crystal, charge carriers, that is, electrons and holes, are generated by the irradiation with photons with an energy corresponding to the band gap of approximately 4 eV. These carriers migrate in the crystal through the wires.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first centers on tailoring of the size, shape, and threedimensional organization of TiO 2 particles [1,2,11,12] or of Ti-O-Ti wires with semiconductor character. [5,[13][14][15][16] The second strategy focuses on improving the photocatalytic properties: i) by incorporating metal cations and anions (mainly nitrogen, sulphur, iodine, and other elements) into the bulk; [6,14,[17][18][19][20][21][22][23] ii) by supporting metal particles (mainly Au, Ag, Pt, Ni). [1,3,[24][25][26][27][28][29][30][31] Interesting results are obtained when the two abovementioned research directions are combined to benefit from the sum of their advantages.…”
mentioning
confidence: 99%